Went to London, took the dog : the diary of a 60 year-old runaway - Stibbe, Nina (Picador, 2024)
Twenty years after leaving London, Nina Stibbe is back in town with her dog, Peggy. Together they take up lodging in the house of writer Deborah (Debby) Moggach in Camden for 'a year-long sabbatical'. It's a break from married life back in Cornwall, or even perhaps a fresh start altogether. Nina is not quite sure yet. Debby does not have many demands - only to water the garden, watch for toads, and defrost the odd pie - so Nina is free to explore the city she once called home. Between scrutinising her son's online dating developments, navigating the politics of the local pool, and taking detergent advice at the laundrette, this diary of a sixty-year-old runaway reunites us with the inimitable voice of 'Love', Nina, as the writer becomes, as she puts it, 'a proper adult' at last.